2020
DOI: 10.20467/humancaring-d-19-00055
|View full text |Cite
|
Sign up to set email alerts
|

Patient Participation in Nursing Homes: A Meta-Synthesis Review

Abstract: The aim of this study is to gain insight, from a caring science perspective, regarding what patient participation means to older residents in nursing homes. Patient participation must be safeguarded by nurses, but this cannot be done without considering the patient's point of view. The research question is as follows: What does patient participation mean to elderly nursing home residents from a caring science perspective? Using a meta-synthesis approach, seven primary studies are chosen for a hermeneutical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The older adults' possibilities to participate vary depending on the healthcare staffs' ability to invite them to participate, and this affects their feeling of self-determination and security [15]. The participation of older adults can be supported and encouraged by the professional healthcare staff creating good care relationships [16]. Previous studies show that being shown respect as well as the healthcare staffs' ability to invite participation provides a basis for security [15].…”
Section: Introductionmentioning
confidence: 99%
“…The older adults' possibilities to participate vary depending on the healthcare staffs' ability to invite them to participate, and this affects their feeling of self-determination and security [15]. The participation of older adults can be supported and encouraged by the professional healthcare staff creating good care relationships [16]. Previous studies show that being shown respect as well as the healthcare staffs' ability to invite participation provides a basis for security [15].…”
Section: Introductionmentioning
confidence: 99%